Significant cognitive decline in Parkinson's disease exacerbates the reliance on visual feedback during upper limb reaches. (16th July 2021) - Cosgrove, Jeremy; Hinder, Mark R.; St George, Rebecca J.; Picardi, Chiara; Smith, Stephen L.; Lones, Michael A.; Jamieson, Stuart; Alty, Jane E.
Abstract: While upper limb reaches are often made in a feed-forward manner, visual feedback during the movement can be used to guide the reaching hand towards a target. In Parkinson's disease (PD), there is evidence that the utilisation of this visual feedback is increased. However, it is unclear if this is due solely to the characteristic slowness of movements in PD providing more opportunity for incorporating visual feedback to modify reach trajectories, or whether it is due to cognitive decline impacting (feed-forward) movement planning ability. To investigate this, we compared reaction times and movement times of reaches to a target in groups of PD patients with normal cognition (PD-NC), mild cognitive impairment (PD-MCI) or dementia (PD-D), to that of controls with normal cognition (CON-NC) or mild cognitive impairment (CON-MCI). Reaches were undertaken with full visual feedback (at a 'natural' and 'fast-as-possible' pace); with reduced visual feedback of the reaching limb to an illuminated target; and without any visual feedback to a remembered target with eyes closed. The PD-D group exhibited slower reaction times than all other groups across conditions, indicative of less efficient movement planning. When reaching to a remembered target with eyes closed, all PD groups exhibited slower movement times relative to their natural pace with full visual feedback. Crucially, this relative slowing was most pronounced for the PD-D group, compared to the PD-MCI and PD-NC groups, suggesting that substantial cognitive decline in PD exacerbates dependence on visual feedback during upper limb reaches. Highlights: Reach movements were examined in Parkinson's and controls under varied conditions. Planning and execution are impacted by PD and associated cognitive decline. PD patients with dementia had significantly prolonged reaction times when reaching. PD patients had longer movement times when reaching without visual feedback. The prolongation in movement time was greatest in the PD group with dementia.